Assessing Moderating Effects of Board of Directors and Sharia Committee in Improving Performance of Islamic Insurance Company - Kusmayadi, Dedi; Firmansyah, Irman (SMART Insight, 2021)
This study aims to examine the variables of the board of directors and the sharia committee in relation to the variables that affect the financial performance of sharia insurance companies in Indonesia. This research is important because the Islamic finance industry must be run in accordance with the principles of Islamic sharia so that the business that is run is not entirely business. This research was conducted at Islamic insurance companies and insurance companies that run sharia business units in the period 2011 to 2017. The research method used moderated regression analysis. The variable used to measure financial performance is a surplus on contribution (SoC) while the independent variable is a debt to equity ratio, size, and age. The results showed that size has a positive effect on financial performance, age has a negative effect on financial performance, and leverage has no effect on financial performance. Whereas the board of directors strengthens the relationship between leverage and financial performance and weakens the relationship between size and financial performance, and sharia committee weakens the relationship between size and financial performance and strengthens the relationship between age and financial performance.